Idiopathic myelofibrosis with extramedullary hematopoiesis in the kidneys - Schnülle, Peter; Waldherr, Rüdiger; Lehmann, Karl-Jürgen; Woenckhaus, J.; Back, Walter; Niemir, Z.; Woude, Fokko J. van der (Clinical nephrology, 1999)
Extramedullary hematopoiesis is a common finding in idiopathic myelofibrosis and is usually found in liver and spleen. We report on a patient with biopsy-proven myeloid metaplasia and fibrosis of the renal parenchyma as a rare cause of chronic renal failure. The renal biopsy specimen showed numerous infiltrates of hematopoietic cells expressing growth factors like M-CSF, GM-CSF, IL-1beta and PDGF while TGF-beta was not elevated. These findings suggest that hematopoietic growth factors play a key role in the pathogenesis of this condition causing proliferating fibrosis and enlargement of the kidneys.